Adisa O La Storia Dei Mille Anni . Adisa or a Thousand Years Story - D'orzi, Massimo D. (Italy, 2004)
Duration: 01:19:16 A voyage among men, women, and children of the Romany people in Bosnia Hercegovina, documenting the reality and the present life in a country still wounded by the consequences of the war.